Informe de suficiencia profesional aplicada a la industria del sector eléctrico y gestión de la energía - Nakashima Burmester, Julio Tomas (2022)
A systems engineer graduated from the University of Lima is prepared to provide solutions to the needs of organizations in an ethical, socially responsible and professional manner. He is constantly learning and updating about emerging information technologies to integrate them in the management of business processes, in the different solutions that he manages and implements. I started my professional development very early, even as a career student, performing roles that correspond to the Software Engineering training area. In this initial period of work experience, my main achievements were in the development of customized client-server software and in different business areas, depending on the origin of the requesting client. Years later I went on to perform roles related to the areas of training in Information Technology and Information Systems, becoming a manager in the systems area of the organization in which I currently work. I had the opportunity to lead and participate in many projects during the 15 years in which I assumed Systems Management. Among the main projects I was in charge of are the Extranet solutions for the commercial development of the company, installation and migration of CRMs and ERPs, development of the company's Datawarehouse, among others. In recent years I have developed extensive experience in the areas of training in Business Engineering and Information Systems, leading the Digital Transformation strategy of the company both internally and that of our partners, in implementations of business intelligence tools to support in decision making. In the last four years of my professional career, I led the implementation strategy and analysis development of Sell Out and Inventory in the company's distribution channel. This report will detail the most important achievements of each stage of my professional experience, identifying each of the capacities that a systems engineer must achieve in the associated roles.